Off-central acceptor impurity in a spherical quantum dot - Boichuk, V.I.; Leshko, R.Ya.; Bilynskyi, I.V.; Turyanska, L.M. (Condensed Matter Physics, 2012)
The hole energy spectrum with the ion of an acceptor impurity in the quantum dot has been calculated using the spherical approximation of the multiband Luttinger model. The dependence of the hole energy levels on the impurity location in the quantum dot has been studied. The effect of the impurity location on the dipole momentum and the oscillator strength has been analyzed. The hole interlevel absorption coefficient has been calculated. У рамках сферичного наближення багатозонної моделi Латтiнджера проведено обчислення енергетичного спектру дiрки за наявностi iона акцепторної домiшки у сферичнiй квантовiй точцi. Дослiджено залеж-нiсть енергетичних рiвнiв дiрки вiд розташування домiшки у наносистемi. Проаналiзовано вплив положення домiшки на дипольний момент та силу осцилятора мiжрiвневих переходiв. Визначено коефiцiєнт поглинання свiтла, зумовлений мiжрiвневими переходами дiрки.